Correction to: Influence of cancer and acute inflammatory disease on taste perception: a clinical pilot study (Supportive Care in Cancer, (2019), 27, 4, (1579), 10.1007/s00520-019-4642-6) - Schalk, Priska; Kohl, M.; Herrmann, H. J.; Schwappacher, R.; Rimmele, Martina; Büttner, Andrea; Neurath, Markus; Zopf, Yurdagül; Siebler, Jürgen (Supportive Care in Cancer, 2020)
The Acknowledgement Statement was incorrect in the original publication of this article [1] and the previous correction note [2]. The correct statement is as follows:
CRIS-Team Scopus Importer:2020-02-28